Effect of water temperature on the morbidity of Tetracapsuloides bryosalmonae (Myxozoa) to brown trout (Salmo trutta) under laboratory conditions. Issue 7 (3rd March 2021) - Waldner, Karoline; Borkovec, Martin; Borgwardt, Florian; Unfer, Günther; El‐Matbouli, Mansour
Abstract: Proliferative kidney disease (PKD) is a disease found in salmonid fish that is widespread in Europe and North America. The dependency of the clinical signs on the water temperature is extensively reported in rainbow trout, but detailed information on brown trout is lacking. In this study, juvenile brown trout were exposed to the spores of Tetracapsuloides bryosalmonae and then kept at different ambient water temperatures (16°C, 19°C and 22°C) for 10 weeks along with recording of morbidity throughout the experiment. At 6, 8 and 10 weeks post‐exposure, fish from each temperature group were sampled and underwent pathoanatomical examination to survey disease progression. At 16°C, brown trout showed a significantly higher survival probability compared to those kept in 19°C and 22°C water. Additionally, the parasitic burden (MSQ) was higher and the clinical signs were more pronounced in the brown trout kept at 19°C and 22°C compared with the ones kept at 16°C. This study highlights the correlation of PKD outbreaks and water temperature increases related to global climate change, which will impact the future distribution of brown trout in natural waters.